How the coarse fraction influences the microstructure and the effective thermal conductivity of alumina castables – An experimental and numerical study. Issue 1 (January 2018) - Fruhstorfer, Jens; Demuth, Cornelius; Goetze, Pitt; Aneziris, Christos G.; Ray, Subhashis; Gross, Ulrich; Trimis, Dimosthenis
Abstract: This study investigates the particle size distribution's effect on the microstructure and effective thermal conductivity (ETC) of alumina castables. The ETC was measured by the transient plane source method and predicted numerically based on a two-scale model describing the structure on a fine and coarse scale. The prediction considered particle and pore size distributions, porosity (around 20%) and grain morphology. The microstructure was investigated by scanning electron microscopy. For a constant fines content, increasing the coarse grain fraction while decreasing the medium fraction enhanced sintering of the matrix. Small pores (≤250 nm) increased the sintering activity. The densest castable contained the most small pores. The particles' and pores' contributions to the sintering activity led to intensified microcracking and a decreased ETC. The numerical model did not consider constituents ≤500 nm like the small pores and microcracks and the calculated ETC values consequently deviated from the measured values.